FTIR, Raman spectra and ab initio calculations of 2-mercaptobenzothiazole - Rai A.K.; Singh R.; Singh K.N.; Singh V.B. (My University, 2025)
FTIR and Raman spectra of a rubber vulcanization accelerator, 2-mercaptobenzothiazole (MBT), were recorded in the solid phase. The harmonic vibrational wavenumbers, for both the toutomeric forms of MBT, as well as for its dimeric complex, have been calculated, using ab initio RHF and density functional B3LYP methods invoking different basis sets upto RHF/6-31G** and B3LYP/6-31G** and the results were compared with the experimental values. Conformational studies have been also carried out regarding its toutomeric monomer forms and its dimer form. With all the basis sets the thione form of MBT (II) is predicted to be more stable than thiol form (I) and dimeric conformation (III) is predicted to be more stable with monomeric conformations (I) and (II). Vibrational assignments have been made, and it has been found that the calculated normal mode frequencies of dimeric conformation (III) are required for the analysis of IR and Raman bands of the MBT. The predicted shift in NH- stretching vibration towards the lower wave number side with the B3LYP/6-31G** calculations for the most stable dimer form (III), is in better agreement with experimental results. The intermolecular sulfur-nitrogen distance in N-H⋯S hydrogen bond was found to be 3.35 Å from these calculations, is also in agreement to the experimental value. © 2005 Elsevier B.V. All rights reserved.